In Silico Drug Discovery on Dengue Hemorrhagic Fever Using Tetracycline Analogues - R. Balajee; Dr. M. S. Dhanarajan PhD (International Journal of Pharma and Bio Sciences, 2010)
Dengue hemorrhagic fever is caused by four different serotypes of Dengue virus (DEN-1, DEN-2, and DEN-3, DEN-4). Dengue virus comes under the family flaviviridae. The Dengue infection usually shows severe head ache, fever, rashes all over the body and finally leads to death. Dengue hemorrhagic fever has high motality rate. Tetracycline is found to inhibit the activity of envelope protein during virus entry. The analogues of tetracycline are drawn using ISIS Draw. The energy of those analogues is calculated by using ChemDraw. The docking studies are analyzed and concluded a new molecule is found to have lowest energy potential during docking.